Transference of RXam2 and Bs2 genes to confer resistance against cassava bacterial blight (CBB) (2016)
Abstract. Cassava bacterial blight (CBB), caused by Xanthomonas axonopodis pv. manihotis (Xam), is a major disease in all regions where cassava is cultivated. To generate broad spectrum and durable CBB resistance it is necessary pyramiding several R genes. We have identified two candidate resistance genes, named RXam1 and RXam2 which colocalize with QTLs associated to resistance against Xam. RXam1 codes for a RLK (Receptor-Like Kinase) protein. We generated several transgenic cassava lines overexpressing RXam1. In vitro plants of three lines showed reduced symptoms and reduced bacterial growth after Xam infection with strain CIO136 compared to empty vector transgenic plants. The second cassava gene, RXam2, codes for a NB-LRR protein. Using RNAi we generated RXam2-silenced transgenic plants, which were more susceptible to several Xam strains than non-transformed plants. On the other hand, plants overexpressing RXam2 showed reduced symptoms to Xam strains. These data collectively suggest that RXam2 is a resistance gene against Xam. In addition, an autoactive version mutated in the MHD motif (NB domain) of RXam2 was generated through site directed mutagenesis and was able to generate a Hypersensitive Response (HR) by transient agroinfiltration in cassava and tobacco leaves. The autoactive version of RXam2 was cloned under a TALE1Xam-inducible promoter and transient expression in tobacco showed a strong HR when co-infiltrated with a plasmid containing the TALE1Xam gene. Several independent transgenic stable lines are being evaluated to assess TALE1Xam inducibility. Finally, several cassava transgenic plants overexpressing Bs2 from pepper were obtained and showed constitutive, typical immune responses.